Contextualising Conferences: Ten Reflections on Ten Years of Swedish Local Authority Events on “Masculinity in Change” - Hearn, Jeff (Socialmedicinsk tidskrift, 2020)
Abstract: This article reflects on the ten-year long series of one-day conferences, Maskulinitet i förändring [Masculinity in change] organised by Länsstyrelsen i Örebro län (county), beginning in 2010, in terms of considering these questions: is this a unique phenomenon and achievement? How do we explain it? How do we understand it? In response, the main issues discussed are: the context of and background to the conferences series; the nature of conferences themselves; relations to the state and local state; geographical location; framings and words used in organising the conferences; political and policy orientations of the conferences; the range and gender of invited speakers; the frequency of working across sectoral boundaries; topics addressed and possible gaps; and the impact and interrelations of key individual and institutions.